Preparation and characterization of hematite decorated carbon nanostructures for photoelectrochemical water splitting application / Nur Maisarah Abdul Rashid - Nur Maisarah, Abdul Rashid (2019)
This current study presents reports on the synthesis, characterization and evaluation of the hybrid hematite decorated carbon nanostructures composites (α-Fe2O3/CNs) as the anode material for application in a photoelectrochemical (PEC) water-splitting device. The α-Fe2O3/CNs nanocomposites were prepared by using two separate techniques for the two component materials. The CNs component was prepared on nickel (Ni) foil substrate by radio frequency plasma assisted hot wire chemical vapour deposition system. The morphology and yield of CNs generated from plasma decomposition of methane diluted hydrogen gas on Ni foils pre-treated by argon gas at different RF powers were investigated in the initial part of the work. The formation of Ni clusters as the base structure to provide the grain boundary and nucleation sites for the growth of CNs has strong influence on the morphology and yield of CNs. The initial formation of highly-folded and widely-wrapped multilayer graphitic sheets plays a crucial role in assembling various morphologies of CNs in the form of clusters, caterpillar-like and granular structures. Hydrogen plasma etching effect promotes the formation of CNs with large surface area attributed by the defective open edges graphitic nanosheets. This morphology serves as a matrix for the incorporation of cubic α-Fe2O3 for the formation of the nanocomposite in the second stage of this work. This stage involves the decoration of high quality single crystal α-Fe2O3 nanocubes onto various CNs surfaces via hydrothermal approach. Prior to the deposition process, ideal conditions in producing single-crystalline α-Fe2O3 nanocubes with well-defined shape had been identified by varying the heating duration of the hydrothermal process. During the decoration process, α-Fe2O3 are found to be randomly distributed on the CNs and this hybrid nanocomposites had been used as the photo-anode in the PEC device application. The unique structure of α-Fe2O3/CNs synthesized on Ni foils pre-treated at RF powers of 60, 80, 120 and 140 W exhibit improved PEC properties as-compared to CNs when used as anode material from analysis of the linear sweep voltammetry, Mott Schottky analysis and chronoamperometry results. However, optimum properties of CNs deposited on Ni foil pre-treated at RF power of 100 W shows the most optimum PEC performance. The more defective and less ordered structure of the CNs were believed to contribute to such performance. Furthermore, the high surface area of caterpillar-like CNs acts as a solar trapping agent to harness visible light absorption. The results from this study can serve a feasible and robust model in producing hybrid α-Fe2O3/CNs nanocomposites that can be used as active material for photo-anode in water-splitting device for clean- and green-energy production.